EAT-UpTF: Enrichment Analysis Tool for Upstream Transcription Factors of a Group of Plant Genes - Shim, Sangrea; Seo, Pil Joon (Frontiers in Genetics, 2020)
EAT-UpTF (Enrichment Analysis Tool for Upstream Transcription Factors of a gene group) is an open-source Python script that analyzes the enrichment of upstream transcription factors (TFs) in a group of genes-of-interest (GOIs). EAT-UpTF utilizes genome-wide lists of TF-target genes generated by DNA affinity purification followed by sequencing (DAP-seq) or chromatin immunoprecipitation followed by sequencing (ChIP-seq). Unlike previous methods based on the two-step prediction of cis-motifs and DNA-element-binding TFs, our EAT-UpTF analysis enabled a one-step identification of enriched upstream TFs in a set of GOIs using lists of empirically determined TF-target genes. The tool is designed particularly for plant researches, due to the lack of analytic tools for upstream TF enrichment, and available at https://github.com/sangreashim/EAT-UpTF and http://chromatindynamics.snu.ac.kr:8080/EatupTF.